Pencerahan Hukum Kepada Masyarakat Desa Rotnama - Yeheskel Wessy; Stelvia W. Noya; Micael Ririhena (Lembaga Pengembangan Kinerja Dosen, 2024)
Criminal law is a branch of law that regulates crimes and violations and the sanctions that can be imposed on perpetrators. A good understanding of criminal law is very important for society to be able to avoid acts that violate the law and understand their rights and obligations as citizens. Criminal law is a collection of rules that determine what actions are prohibited and subject to criminal sanctions. Actions that are categorized as criminal acts can include crimes and violations. Regarding this matter, it is deemed necessary by the Rotnama Village Government, Mdonahiera District, Southwest Maluku Regency to schedule it as a form of cooperation in implementing service to the Rotnama Village Community through socialization with the theme